Health and economic evaluation of cytomegalovirus vaccination strategy among young women in China: a modelling study - Bin Zhang; Gang Qin; Jun-Tao Shu; You-Jia Wu; Yin-Hua Jiang; Yi-Wen Ge; Meng-Zhao Yin (BMJ Public Health, 2025)
Background Congenital cytomegalovirus (cCMV) infection imposes a substantial economic burden on both families and society in China. There is currently a paucity of dynamic models to study cytomegalovirus (CMV) vaccination strategies for China’s high-seroprevalence population (over 95%). Recent clinical trials demonstrated that the messenger RNA (mRNA) vaccine candidate, mRNA-1647, exhibited potential efficacy in both preinfection and postinfection contexts. This study aims to assess the cost-effectiveness of various CMV vaccination strategies for Chinese young women.Method An age-structured dynamic model was adopted, using Mathematica software, to simulate three strategies: (1) no vaccination (status quo); (2) pre-marriage vaccination (age 20–28 years); (3) reproductive-age vaccination (age 20–40 years). The vaccine was assumed to have 50% coverage and 50% efficacy for the first 5 years, with efficacy gradually decreasing over the next 15 years, costing US$300 per treatment course. This study period covers 2025–2050. Health outcomes included reductions in cCMV infection incidence, morbidity and mortality. We conducted cost-effectiveness, scenario and sensitivity analyses, discounting costs and disability-adjusted life years (DALYs) at 3% annually. The strategy would be considered cost-effective if the incremental cost-effectiveness ratio (ICER) was below China’s 2023 per capita gross domestic product (US$12 675).Results By 2050, pre-marriage and reproductive-age vaccination strategies could prevent cCMV infection incidence by 38.8% (95% uncertainty interval [UI], 33.7% to 43.5%) and 43.3% (38.3% to 47.1%), respectively, with ICERs of US$4751 (4124 to 5378) and US$10 814 (10 290 to 11 338) per DALY averted compared with the status quo. However, the reproductive-age strategy is not cost-effective, with an ICER of US$25 553 (12 566 to 36 126) versus the pre-marriage strategy.Conclusions Prioritising pre-marriage vaccination could control cCMV infection in China. Our findings would inform public health policies and guide future research on optimising CMV vaccination strategies.